Christian Extremism in Europe and its Impact on Technological Advancement - Greta Iris (GoAcademica Research & Publishing, 2023)
Europe has been a cradle of technological innovation for centuries. However, in recent times, the continent has witnessed the rise of Christian extremism that poses challenges to the progress of technology. This article explores the phenomenon of Christian extremism in Europe and its implications for technological development. It delves into the reasons behind this extremism, its impact on innovation, and possible strategies to address the issue.